Rectal Hemorrhage Revealing Rectal Cancer After Anticoagulation in A Patient with Acute Coronary Syndrome - ABDELBAKI, Mr.; KHELLAFI, N. (Clinical Medicine And Health Research Journal, 2023)
Cardiovascular diseases and cancer are the leading causes of mortality worldwide. The concomitant presence of cancer and acute coronary syndrome is not uncommon, ranging from 1.9% to 4.2%. We report our experience in a patient suffering from an acute coronary syndrome treated by medical treatment where the use of anticoagulants caused rectal bleeding revealing rectal cancer.